The prospect of implementing safety education in Malaysian primary schools: from the perspective of school administrators - Ismail, Khamsiah; Mohamad Shukri, Muhamad Farhan; Badzis, Mastura; Ssekamanya, Siraje Abdallah (EUSER-European Center for Science Education and Research, 2016)
Despite of the various attempts to implement safety practices in school, there still many unresolved issues related to students’ safety in schools. This study aimed to explore and examine current safety management practices in Malaysian primary schools and the type of safety management plans adopted by the administrators for ensuring students’ safety. The sample of this study consisted of 141 School Headmasters and Deputy Headmasters (Administration and Curriculum, Student Affairs or Co-curriculum), randomly selected from 138 primary schools in Kuala Lumpur and Selangor, Malaysia. Quantitative methods were used and the data of school administrators’ attitude and stances in implementation of safety management practices were gathered using a set questionnaire. The data was then tabulated,summarized and evaluated to draw conclusions from them, using the Statistical Package for the Social Science (SPSS).Results from the study indicated that there was a strong positive attitude among school administrators in relation to safety management plan and policy practices in school. Teachers’ and staffs’ participation and parental and community involvement are significantly and positively predicted by school administrators’ commitment and communication; as well as safety education, training and campaign at schools. Some of the safety practices investigated in the study were not observed in schools due to increasing workload and responsibilities of teachers and their time availability. Safety practices at the schools mostly depended on the issues that are considered as important by the respective schools. As the implication of this study, some recommendations were made to help schools to improve safety practices at school and promote cooperation between school administrators, teachers, parents and community as a whole. The study also implied that implementation of safety management education in Malaysian primary school has a good prospect.